New designs of prostheses for patients after exarticulation of hand in the radiocarpal joint - Litvinenko, Oksana; Yarovoy, Yevgeny; Skripka, Olexiy; Kuzin, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Problems of making prostheses for patients with amputation defects on the level of exarticulation in the radiocarpal joint, as well as designs of the above prostheses and their elements are analysed.